SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENDUDUK PENERIMA RASKIN DI KECAMATAN MUARA PAPALIK JAMBI: Decision Support System;Fuzzy Logic;MySQL;Raskin;Visual Basic 6.0;Weighted Product Method - Louis, Ahmad; Yuriska, Hesti (JURNAL AKADEMIKA, 2020)
In Indonesia rice program for poor families called by the term raskin. Raskin program is one of the goverment’s efforts to reduce expenditure burden of poor families. But in practice his field, decision-making criteria to determine the recipient of rice that has accurred generally does not refer to the criteria of poor families, resulting int the distribution of rice is misplaced. Fuzzy logic is a method us in this research is the method of Fuzzy Multi-Attribute Decision Making (FMADM), and methods used in FMADM in Weighted Product method (WP). Development of data processing built using Visual Basic 6.0 programming languange and uses MySQL database input an output. The result achieved in this study is a decision support sysem raskin division is right on target and in accordance with the specified criteria. Thereby minimizing froud in the distribution of rice for the poor.